2019
DOI: 10.5815/ijisa.2019.12.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Performance of Naive Bayes And Decision Tree Classification Using R

Abstract: The use of technology is at its peak. Many companies try to reduce the work and get an efficient result in a specific amount of time. But a large amount of data is being processed each day that is being stored and turned into large datasets. To get useful information, the dataset needs to be analyzed so that one can extract knowledge by training the machine. Thus, it is important to analyze and extract knowledge from a large dataset. In this paper, we have used two popular classification techniques-Decision tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…For example, recent research by Maswadi et al, (2021) shows that NB and DT classification algorithms are used to classify human activities such as: sitting, standing, walking, sitting down, and standing up which improved accuracy and effectiveness. Yadav and Thareja, (2019) compare the performance of naive Bayes which use an assumption that the pair of features being classified are independent and DT classification uses a divide and conquer by calculating the accuracy of each technique using the R language.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent research by Maswadi et al, (2021) shows that NB and DT classification algorithms are used to classify human activities such as: sitting, standing, walking, sitting down, and standing up which improved accuracy and effectiveness. Yadav and Thareja, (2019) compare the performance of naive Bayes which use an assumption that the pair of features being classified are independent and DT classification uses a divide and conquer by calculating the accuracy of each technique using the R language.…”
Section: Related Workmentioning
confidence: 99%
“…This is due to their good performance and high accuracy in classifying obesity levels compared to SVM and KNN. DT is a high-performance classification algorithm that analysed data and uses a representation in a tree structure to gain a better insight into the data (Yadav & Thareja, 2019). NB is a classification technique based on the Bayes Theorem with an assumption of independence among predictors.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is selected because several studies have shown that the Naïve-Bayesian method yields better overall evaluation result compared to other supervised learning methods. An experiment that compared the performance of Decision Tree and Naïve-Bayes algorithm in classifying student performance data indicated that Naïve-Bayes achieved higher accuracy and classi ed the values closer than Decision Tree [6].…”
Section: ) Mappingmentioning
confidence: 99%
“…This paper [20] provides an overview of the decision tree and the Naive Bayes classification. The research utilized the student's output classification dataset to demonstrate how a decision tree and naive can be constructed and the principle of both classification strategies.…”
Section: A Application Of Naï Ve Bayes Algorithmmentioning
confidence: 99%